Cellulose fibers coated zirconium oxide: Characteristics, technology and performance - Mulinari, Daniella R.; Pereira, Paulo Henrique F. [UNESP]; Resende, Juliana M. (My University, 2012)
Actually, technologies require materials with a combination of properties that areńt found in conventional materials. Thus, the hybrid materials (combination of organic and inorganic constituents) emerge as an alternative for the production of new multifunctional materials with a range of applications. These organic-inorganic materials are of great interest in commercial applications due to its mechanical properties, optical and thermal, that combine thermal and chemical stability of ceramic materials with the processability and flexibility of organic compounds and polymers. Metal oxides are of great interest because of their chemical and electrical properties. The use of asymmetric particles from vegetable biomass coated metal oxide has attracted attention in the academic world. Cellulose fibers present many intrinsic advantages, such as low cost, availability, bio-degradability, and easy handling. However, the polymer is relatively inert as the hydroxyl groups responsible for most of the reactions with organic and inorganic reagents are involved in extensive inter- and intramolecular hydrogen bonding. In order to make cellulose more reactive, surface modification were prepared with many metal oxides. Experimental methodology of the coating process depends on the form the cellulose is obtained, fibers or membrane. In the fibers form, the treatment of cellulose with a precursor reagent can be made in aqueous or non-aqueous solvent. In this chapter will reported ZrO2.nH2O particles coated cellulose fibers from sugarcane bagasse obtained by fiber for use as reinforcement in polymer matrix and heavy metal adsorption.